Evaluasi Kebijakan Peradilan Elektronik (E-Court) Mahkamah Agung Republik Indonesia - Ariwijaya, Abdul Rachmat; Samputra, Palupi Lindiasari (Jurnal Hukum & Pembangunan, 2021)
This study aims to evaluate the administrative policies and electronic trial (E-Court) of the Supreme Court of the Republic of Indonesia and the judicial bodies under it in achieving the principles of administering judicial power, namely: simple, fast, and low-cost justice. The research method uses a retrospective evaluation theory that directs the present results after implementing the E-Court policy. The data used consisted of secondary data (documents) and primary data through in-depth interviews from experts and E-Court policymakers. The results showed that the E-Court policy succeeded in clarifying the Supreme Court of the Republic of Indonesia's organization in realizing simple, fast, and low-cost judicial principles, both for the internal judiciary and the justice-seeking community. Indicators of the realization of simple judicial principles can describe at the stage of registering cases which are carried out quickly through an electronic system